How do topics and emotions develop in elementary school children? A text mining perspective based on free-writing text over 6 years - Liu, Mengjun; Jiang, Xinyu; Zhang, Bingbing; Song, Ting; Yu, Gang; Liu, Guofang; Jiang, Nan; Wu, Di; Zhou, Zhi (Frontiers in Psychology, 2023)
Free-text data with long duration and continuity have great potential for studying environmental concerns and emotional expressions in child development. Based on ecosystem theory, using topic modeling and sentiment analysis in text mining to mine 4556 free-text writing data from first to sixth grade in elementary school, this study aims to reveal concerned topics’ evolutionary trends and sentiment expression differences in topics during elementary school children’s development. The results show the following: (1) Children prefer to focus on the topics of school and family in elementary school; (2) With the growth of grades, the proportion of family topics continues to decline, while that of social culture topics keeps rising; (3) When describing school, family, social culture, and interest, children mostly express negative emotions, and when describing peers and ability they mostly express positive emotions; (4) As the grade increases, the emotional expression on social culture topics become negative, while that on ability and interest topics become positive, and there are more differences in emotion expression between topics in junior and senior elementary grades. Discussion and conclusion are discussed at the end.